The Impact of Longevity Improvements on U.S. Corporate Defined Benefit Pension Plans - Kiff, John (IMF Working Papers; Working Paper, 2012)
This paper provides the first empirical assessment of the impact of life expectancy assumptions on the liabilities of private U.S. defined benefit (DB) pension plans. Using detailed actuarial and financial information provided by the U.S. Department of Labor, we construct a longevity variable for each pension plan and then measure the impact of varying life expectancy assumptions across plans and over time on pension plan liabilities. The results indicate that each additional year of life expectancy increases pension liabilities by about 3 to 4 percent. This effect is not only statistically highly significant but also economically: each year of additional life expectancy would increase private U.S. DB pension plan liabilities by as much as USD 84 billion.